Gases emissions estimation and analysis by using carbon dioxide balance method in natural-ventilated dairy cow barns - Zou, Bing; Shi, Zhengxiang; Du, Songhuai (International Journal of Agricultural and Biological Engineering, 2020)
Contaminated gases emissions from livestock industry are becoming one of the most significant contributors to the increasingly serious environmental pollution. To find a way to reduce gases emissions, it is essential to reveal the factors that can affect the gases emissions. In this study, the concentrations of typical gases (including ammonia (NH3), carbon dioxide (CO2), hydrogen sulfide (H2S), and sulfur dioxide (SO2)) generated from naturally-ventilated dairy cow barns were detected through the sample-data method in Tianjin, northern China. Indoor environmental conditions, such as temperature (T) and relative humidity (RH), were measured simultaneously. After applying the carbon dioxide mass balance method, ammonia, hydrogen sulfide and sulfur dioxide emissions were determined. The correlation analysis and regression analysis between the climate condition and gas emissions were conducted to assess the data collected in dairy cow barns during the whole study period. There was a significant relationship between environmental conditions and gas emissions. NH3, H2S and SO2 emissions from the building are in the range of 0.98-2.36 g/LU·h, 0-0.034 g/LU·h, and 0-0.069 g/LU·h, respectively. The numerical analysis shows that the NH3 emission is highly correlated with the temperature and relative humidity. The ventilation rate shows a positive correlation with all the three gases. Keywords: gas emissions, environmental conditions, correlation analysis, regression analysis, carbon dioxide, H2S emission, NH3 emission, SO2 emission DOI: 10.25165/j.ijabe.20201302.4802 Citation: Zou B, Shi Z X, Du S H. Gases emissions estimation and analysis by using carbon dioxide balance method in natural-ventilated dairy cow barns. Int J Agric & Biol Eng, 2020; 13(2): 41–47.